Electro-thermal Modeling of Lithium ion Batteries - Gaoussou Hadia Fofana; Youtong Zhang (Institute of Advanced Engineering and Science, 2014)
In this paper, the electro-thermal model of Lithium-ion battery for electric vehicles and its related application were studied. The spatial variations of electrode parameter and the reaction heat generated inside battery must be considered when developing an electro-thermal model of Lithium-ion battery for electric vehicles, to ensure the applicability of the developed model under different operating conditions. The results showed that: with increasing state of charge, the spatial variations of net reaction current density, lithium ion concentration on the surface of active material particles, activation overpotential, equilibrium electrode potential and electrical potential of solid phase are reduced, but the spatial variation of electrical potential of electrolyte phase is enlarged. DOI : http://dx.doi.org/10.11591/telkomnika.v12i5.5016